Correlation of serum amylase level with the severity of acute organophosphorus compounds poisoning - Paul, Gunosindhu; Kabir, Mohammed Ruhul; Kamrul-Hasan, A. B. M.; Ahammed, S. K. Kabir; Hossain, M. Enayet; Ahammed, Ferdaus; Basak, Shishir Kumar; Islam, A. F. M. Nazmul (International Journal of Advances in Medicine, 2021)
Background: Organophosphorus (OP) poisoning is a common mode of suicidal poisoning in our country and is associated with significant mortality and morbidity. Serum amylase has shown a promising role in the assessment of the severity of OP poisoning. We conducted this study to see the association of serum amylase level with acute OP poisoning severity. Methods: This cross-sectional study was conducted among 150 patients admitted with acute OP poisoning to the inpatient department of medicine of a tertiary hospital in Bangladesh from July 2016 to June 2018. Peradeniya organophosphorus poisoning scale was used to detect clinical severity. Serum amylase was measured on the day of admission. Results: The patients' mean age was 23.68±6.80 years, and 65.3% were male. As assessed by the POP scale, 56.7%, 34.7%, and 8.7% of patients had mild, moderate, and severe grades of OP poisoning, respectively. The median serum amylase level was 103.50 (IQR 73.75-156.0) IU/l; 44.7% of the subjects had normal, and 53.3% had an elevated serum amylase. A progressive increase in serum amylase level was observed with the increasing severity of OP poisoning; 77.0 IU/l (IQR 58.0-97.0) in mild grade, 154.0 IU/l (IQR 125.25-162.5) in moderate grade, and 298.0 IU/l (IQR 289.5-305.0) in severe grade and the differences in the median amylase across the three groups were statistically significant (p<0.001). A significant positive correlation between serum amylase level and POP scale score (r=0.970; p<0.001) was also observed. Conclusions: Serum amylase level may be used as a readily available marker of the severity of acute OP poising in resource-poor settings.